Hybrid Camouflaged Anticounterfeiting Token in a Paper Substrate. Issue 4 (21st October 2022) - Ferraro, Antonio; Lio, Giuseppe Emanuele; Bruno, Mauro Daniel Luigi; Nocentini, Sara; De Santo, Maria Penolepe; Wiersma, Diederik Sybolt; Riboli, Francesco; Caputo, Roberto; Barberi, Riccardo Cristoforo
Abstract: Anticounterfeiting of goods is an urgent need both for luxury and cheap everyday life products. Their identification is usually based on overt technologies as printed codes, easy to produce but to be cloned as well. In this work, a standard QR‐code printed on office paper but hidden by a plasmonic multilayer system is exploited. The covert label is then protected by a peculiar reading mechanism, which is only possible in specific illumination conditions. The overall photonic structure consisting of the metal –insulator –metal –insulator, the printed random QR code and the paper substrate results in a strong physical unclonable function (PUF) that provides a multi‐level identification and authentication of goods ensuring uniqueness of nominally quasi‐identical tags and resistance to tampering/cloning attacks. The proposed paper‐based camouflage physical unclonable function (PC‐PUF) can be easily fabricated by low cost and large area techniques paving the way for an easy integration in an industrial supply‐chain as tags devoted to protect consumer merchandises. Abstract : An anti‐counterfeiting tag is experimentally demonstrated on a conformable office paper where a QR code is printed and successively hidden by a plasmonic system. The overall photonic structure leads to a multilevel security tag which can be easily fabricated with low cost and large area techniques, paving the way for easy integration for the protection of several consumer goods.